The Efficacy of Tiotropium as a Steroid-Sparing Agent in Severe Asthma. Issue 3 (2009) - Kapoor, Anmol S; Olsen, Sharla-Rae; O'Hara, Cindy; Puttagunta, Lakshmi; Vethanayagam, Dilini
Abstract : People with severe asthma account for 5% to 10% of all asthmatic patients; however, this small group uses the majority of health care resources. Novel methods are needed to cope with the burden that this minority of patients places on the health care system. A severe asthma clinic patient, who was monitored through the University of Alberta's Virtual Asthma Clinic (Edmonton, Alberta) is presented. Despite optimization of his disease and individualized asthma education (provided by a certified asthma educator), the patient remained on oral glucocorticosteroids (OGS) to control his disease. Following optimization and stabilization, a further reduction in the dose of his OGS by the addition of the long-acting anticholinergic agent tiotropium bromide, was demonstrated. The role of tiotropium as a potential 'steroid-sparing agent' in severe refractory asthma is discussed, noting that if patients who are on OGS are not monitored for active inflammation, they may overuse the amount of prescribed systemic steroids, which can result in long-term steroid-related sequelae.